Implementation of Guidance and Counseling Service Management - Lahmuddin Lubis; Yusuf Hadijaya; Sri Wardani (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
This study aims to describe the Implementation of Guidance and Counseling Service Management in Man 2 Aceh TamiangThis research method is descriptive qualitative using two data collection techniques: interviews and documentation. Data analysis techniques are data reduction, data display, conclusions, and data verification. The results of the study show that the guidance and counseling service program in schools is prepared quite well, even though they develop a service implementation plan using a standard syllabus but the program implemented in the field is quite good. The guidance and counseling service program that has been implemented has referred to the BK 17 plus pattern program and its application is adjusted to the RPL that has been prepared by the guidance and counseling teacher. The implementation of guidance and counseling services at MAN 2 Aceh Tamiang has gone quite well.